Reducing inappropriately suspended VTE prophylaxis through a multidisciplinary shared learning programme and electronic prompting - Christopher Felix Brewer; Dorothy Ip; Emma Drasar; Poureya Aghakhani (BMJ Open Quality)
Background Venous thromboembolism (VTE) is a major cause of preventable hospital death, accounting for up to 10% of inpatient mortality. National guidelines recommend that all patients should be regularly assessed for VTE risk, and prescribed mechanical and pharmacological prophylaxis accordingly. While previous studies have focused on improving prescription uptake on admission, there has been relatively little emphasis on the inappropriate suspension of prophylaxis during inpatient stay.Objective The purpose of this project was to identify the reasons and scale of inappropriate suspension of pharmacological VTE prophylaxis for medical inpatients. We subsequently planned to introduce a number of interventions in order to reduce inappropriate suspension.Methods An initial audit of all medical inpatients was carried out to establish the number with inappropriately suspended pharmacological prophylaxis. We then designed a series of educational meetings and electronic prompting interventions to alert prescribers to these errors, followed by re-audit to assess their efficacy.Results The number of patients with inappropriately suspended VTE prophylaxis was significantly reduced following introduction of our intervention strategy.Conclusions Combined education and electronic email prompts are an effective way of alerting practitioners to reduce inappropriate suspension of VTE prophylaxis. With ongoing teaching and integration of prescribing software alerts, this reduction in VTE prescribing errors could be sustained.